Membangun Budaya Pembelajaran Berkelanjutan Dalam Sumber Daya Manusia 2045: Penerapan Teori Pembelajaran Organisasi - Rohida, Leni; Kasanah, Silviyatun; Stephani, Nadya Salsabila; Bariah, Ainul (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study uses a qualitative method with a descriptive analysis approach to examine the application of organizational learning theory in building a culture of continuous learning in human resources towards 2045. This study also aims to understand how a culture of continuous learning can be improved in organizations and the inhibiting factors faced in this effort. Using secondary data from a literature review collected through Google and Google Scholar, this study explores the concept of organizational performance in the context of continuous learning. The results of the study indicate that Peter Senge's organizational learning theory, which consists of five main disciplines of personal mastery, mental models, shared vision, team learning, and systems thinking, has an important role in building a culture of continuous learning to achieve competent human resources in 2045. In addition, examples of companies in Indonesia and abroad that have successfully implemented an organizational learning culture, such as PT Astra International, Telkom Indonesia, Google, and Toyota, show that the application of this theory can improve human resource skills, strengthen competitiveness, and encourage innovation. This study concludes that despite challenges such as resistance to change and infrastructure limitations, solutions such as open communication, shared vision, and effective collaboration can help organizations overcome these obstacles, so that the implementation of a continuous learning culture can build competent, flexible, and competitive human resources in facing global dynamics.